Freedom to Shape the Language of Collective Agreement Analysed on a Case of Sum Payments - Martin Štefko (Societas et Iurisprudentia, 2019)
Lump-sums payments are used as a touchstone to consider current statutory rules on extra payments for services which were performed outside scheduled work hours, rendered on Saturdays or Sundays or done throughout nights. In his paper, the author claims that respective rules are morally ambiguous and legally complex. They seem to privilege trade unions to harm non-unionized workers. However, trade unions are not able to secure their financial interests as well; they cannot opt out “free riders”.